Emergent universe with interacting fluids and the generalized second law of thermodynamics. (1st May 2015) - Paul, B C; Majumdar, A
Abstract: We investigate the emergent Universe (EU) scenario in the presence of interacting fluids. The nonlinear equation of state (EoS) considered in the general theory of relativity for obtaining the EU is effectively a cosmological model with a composition of three fluids. In this paper, we consider two models to realize viable cosmological scenarios: (i) a two-fluid model with the interaction of a pressureless fluid, with the fluid having the nonlinear EoS needed for the EU, and (ii) a three-fluid model with interaction among the three fluids, which originate from the EoS of the EU. It is found that realistic cosmological models in accordance with observations are not ruled out for both of these cases. We further show that the generalized second law of thermodynamics is found to hold up well in the EU with interacting fluids.